Uwarunkowania integracji monetarnej krajów Europy Środkowej i Wschodniej ze strefą euro - Klamut, Mirosława (Conditions for monetary integration of the countries of Eastern and Central Europe with euro area, 2006)
Entering the monetary union by the countries of Central and Eastern Europe is not only a long term investment in the economic growth of these countries but, it is also a sign of understanding the necessity for carrying many renouncement and adjustment cost. The author in the article considers the advantages and costs of entering the euro area by these new perspective members. It is concluded that a longer membership in the ERM II leads not only to the achievement of a better nominal convergence (at a level of formal criteria) but it also enables a full convergence process to occur. It is further concluded that having the independent monetary policy can compensate for a negative consequence of lower dynamics of the economic development, both for the society and for the economy. The author points to the time asymmetry in the occurring costs and advantages during the process of joining the euro area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 9-24